Analisis Profitabilitas dan Kinerja Keuangan PT Bio Farma Periode 2019-2023 - Naqi, Nadiyatun; Aisyah, Esy Nur (Maliki Interdisciplinary Journal, 2025)
This research aims to analyze the financial performance of PT Bio Farma (Persero) during the 2019-2023 period by highlighting aspects of profitability through analysis of the Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE) ratios. The findings show an increase in performance in 2023, with NPM reaching 13.42%, ROA of 6.42%, and ROE of 12.45%. However, these three ratios are still below industry standards of 20%, 30% and 40% respectively. This indicates the need for improvements in operational efficiency, asset management and capital optimization. Fluctuations in profitability throughout the analysis period reflect various challenges and opportunities that influence business sustainability and company competitiveness in the national pharmaceutical sector.